Implementing legislation for the Protocol on Environmental Protection to the Antarctic Treaty : joint hearing before the Subcommittee on Economic Policy, Trade, and Environment of the Committee on Foreign Affairs and committee on Merchant Marine and Fisheries, House of Representatives, One Hundred Third Congress, first session, November 16, 1993. - United States. Congress. House. Committee on Foreign Affairs. Subcommittee on Economic Policy, Trade, and Environment.; United States. Congress. House. Committee on Merchant Marine and Fisheries. (Washington : U.S. G.P.O. : For sale by the U.S. G.P.O., Supt. of Docs., Congressional Sales Office, 1994)
Mode of access: Internet.